ASSESSMENT OF MATHEMATICS CRITICAL THINKING: A SYSTEMATIC REVIEW - Silky Achilla; Masrukan Masrukan; Iqbal Kharisudin (Prima: Jurnal Pendidikan Matematika, 2026)
This study presents a systematic review of research on the assessment of mathematical critical thinking published between 2018 and 2025. The review was conducted using the PRISMA method to obtain a comprehensive understanding of research characteristics, assessment designs, the dimensions of critical thinking evaluated, and the mathematical content used across various studies. The findings indicate a significant increase in scholarly attention toward mathematical critical thinking, reflected in the growing number of publications across different educational levels and geographic regions, particularly in Asia. The methodological diversity found in the studies, including experimental, quasi-experimental, qualitative, survey-based, and research and development approaches demonstrates that assessing critical thinking requires flexible and context-sensitive strategies. Further analysis reveals that the critical thinking skills evaluated in the studies include analysis, evaluation, interpretation, inference, generalization, mathematical modeling, and argument construction. The mathematical content assessed is similarly varied, ranging from algebra, geometry, statistics, calculus, and discrete mathematics to modeling and complex analysis. These findings show that mathematical critical thinking is a multidimensional competency relevant to all areas of mathematics. Overall, the results highlight the need for developing authentic, valid, and curriculum-aligned assessment instruments to strengthen students’ mathematical reasoning and support the demands of 21st century learning.